PENGARUH PENGALAMAN KERJA, TINGKAT PENDIDIKAN, BUDAYA KERJA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PADA UNIT RAWAT INAP RUMAH SAKIT STELLA MARIS MAKASSAR - Feronica Dwi Cuslinda; Mattalatta Mattalatta; Hasmin Hasmin (AkMen JURNAL ILMIAH, 2015)
The Effect of Work Experience, Education Level, Work Culture and Quality of Service to Patients Satisfaction in Inpatiens Unit Stella Maris Hospital Makassar. This study aimed to know(1) Work experience influence onpatients satisfaction, (2) The education level influence onpatients satisfaction, (3) Thework culture effect onpatients satisfaction, (4) Theservice quality effect on patients satisfaction,(5) Work experience, education level, work culture and influence service quality to the satisfaction of the patient sin the hospital inpatient units Stella Maris Makassar simultan eously. This research was conducted in inpatient hospital units Stella Maris Makassar on10th, 11thand 13th of January 2015.The sample ofthis study used purposive esampling about 37respondents. Quantitative research used analytical survey by distributing questionnaires to analyze the facts and data necessary to support the discussion of research. The results showed that (1) There is anegative effectandno significant work experienceto the satisfaction ofthe patients, (2) There is appositive and no significant effect of educational level to the satisfaction ofthe patients, (3) There is apositiveand no significant influence the work culture of the patients satisfaction,(4) There is apositive and significant impact of service quality on patients satisfaction, (5) There is appositive and significant effect of variable work experience, education level, work culture and quality of service to patients satisfaction in hospital inpatient unit simultaneously Stella Maris Makassar